Psychometric properties of the needs scale for families of adults with intellectual disabilities, Colombian version - Diana Sthefanía Muñoz-Gómez (Colombia Médica, 2023)
Aim: Assess the psychometric properties of reliability and validity of the Family Needs Assessment (FNA) questionnaire designed for adults in Colombia. Conducting research studies to validate the FNA questionnaire in other contexts and age groups is important.Methods: Five hundred fifty-four caregivers of adults with intellectual disabilities participated in the study (298 men and 256 women). The ages of the individuals with disabilities ranged from 18 to 76 years. The authors carried out the linguistic adaptation of the items and cognitive interviews to identify if the items evaluated what was intended. A pilot test with 20 participants was also conducted. An initial confirmatory factor analysis was carried out. Given that, this analysis did not show a good adjustment of the theoretical model initially proposed, an exploratory factor analysis was carried out to elucidate the most appropriate structure for the Colombian population. Results: The factor analysis found five factors, each with a high ordinal alpha (Caregiving and family interaction, social interaction and future planning, Economy, and recreation, independent living skills or autonomy, and Services related to disability). Of the 76 items, 59 were preserved, which had a factorial load greater than 0.40; and 17 were left out because they did not meet this requirement.Conclusion: Future research considers corroborating the five factors found and establishing their clinical applications. Concerning the concurrent validity, the families perceive that high need for social interaction and future planning and little support for the person with an intellectual disability.